Neurologic injuries in boxing and other combat sports - Zazryn, T. R.; McCrory, P. R.; Cameron, P. A. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
Many sports have neurologic injury from incidental head contact; however, combat sports allow head contact, and a potential exists for acute and chronic neurologic injuries. Although each combat sport differs in which regions of the body can be used for contact, they are similar in competitor exposure time. Their acute injury rates are similar; thus their injuries can appropriately be considered together. Injuries of all types occur in combat sports, with injuries in between one fifth to one half of all fights in boxing, karate, and tae kwon do. Most boxing injuries are to the head and neck region. In other combat sports, the head and neck region are the second (after the lower limbs) or the first most common injury site.